Community gout management program needed for adult people in the rural area - Ema Madyaningrum; Fitrina M. Kusumaningrum; Ratri Kusuma Wardani; Annisa Ryan Susilaningrum; Anisah Ramadhani (Journal of Community Empowerment for Health, 2021)
Gout is one of the non-communicable diseases that can affect the quality of life. The high prevalence of gout is apparent in Indonesian research and records in primary health services. However, adult people's needs regarding gout management programs were barely explored. The study aimed to identify the association between the character of demographics, food consumption, and prevalence of gout in the rural areas in The Sleman Regency. This study is a quantitative study using a cross-sectional approach. Samples consisting of 109 adult people were chosen by purposive sampling with inclusion criteria: 1) residents of The Jaranan sub-village, Cangkringan, Sleman, D.I. Yogyakarta Province and 2) age over 25 years old. Data was collected through a survey using questionnaires adapted from the Indonesian Basic Health Survey Questionnaire, Gout Knowledge Questionnaire (GKQ) and Gout Assessment Questionnaire (GAQ), and food frequency form. Association between gout, food consumption, and knowledge were analyzed using the chi-square test.As a result, the prevalence of gout in adult people in rural areas was 18.35%. They have limited knowledge regarding gout diagnosis, treatment, and prevention (66,97%). Half of the respondents reported consuming food with medium content of purine such as tempeh (56%) and tofu (52%), and were not well-hydrated (63.3%). There was a significant relationship between gout and hypertension and meat consumption. Respondents reported they worried about the progress of gout (>70%) they will experience. In conclusion, the prevalence of gout is high in adult people in rural areas. The adult people who did not have formal education, hypertension, and meat consumption have a significant association with gout diseases. There is a need for a gout prevention program to maintain a healthy lifestyle and healthy diet, improve gout-related knowledge and control the progress of gout disease.